Advances in Biodetoxification of Ochratoxin A-A Review of the Past Five Decades - Chen, Wenying; Li, Chen; Zhang, Boyang; Zhou, Zheng; Shen, Yingbin; Liao, Xin; Yang, Jieyeqi; Wang, Yan; Li, Xiaohong; Li, Yuzhe; Shen, Xiao L. (Frontiers in Microbiology, 2018)
Ochratoxin A (OTA) is a toxic secondary fungal metabolite that widely takes place in various kinds of foodstuffs and feeds. Human beings and animals are inevitably threatened by OTA as a result. Therefore, it is necessary to adopt various measures to detoxify OTA-contaminated foods and feeds. Biological detoxification methods, with better safety, flavor, nutritional quality, organoleptic properties, availability, and cost-effectiveness, are more promising than physical and chemical detoxification methods. The state-of-the-art research advances of OTA biodetoxification by degradation, adsorption, or enzymes are reviewed in the present paper. Researchers have discovered a good deal of microorganisms that could degrade and/or adsorb OTA, including actinobacteria, bacteria, filamentous fungi, and yeast. The degradation of OTA to non-toxic or less toxic OTα via the hydrolysis of the amide bond is the most important OTA biodegradation mechanism. The most important influence factor of OTA adsorption capacity of microorganisms is cell wall components. A large number of microorganisms with good OTA degradation and/or adsorption ability, as well as some OTA degradation enzymes isolated or cloned from microorganisms and animal pancreas, have great application prospects in food and feed industries.